Nano computing revolution and future prospects - Hirwani, Deepti; Sharma, Anuradha (Recent Research in Science and Technology, 2012)
There are several ways nanocomputers might be built, using mechanical, electronic, biochemical, or quantum technology. It is unlikely that nanocomputers will be made out of semiconductor transistors (Microelectronic components that are at the core of all modern electronic devices), as they seem to perform significantly less well when shrunk to sizes under 100 nanometers.The research results summarized here also suggest that many useful, yet strikingly different solutions may exist for tolerating defects and faults within nanocomputing systems. Also included in the survey are a number of software tools useful for quantifying the reliability of nanocomputing systems in the presence of defects and faults.